2017
DOI: 10.1111/jch.13097
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme inhibitor–induced angioedema: A review of the literature

Abstract: According to the National Health and Nutrition Examination Survey 2012, one third of antihypertensive prescriptions in the United States in the past decade were for angiotensin-converting enzyme inhibitors (ACEIs). An important and serious side effect of ACEIs is angioedema caused by a reduction in bradykinin degradation. In a national medical chart abstraction study conducted at the US Veterans Affairs Health Care System in 2008, 0.20% of ACEI initiators developed angioedema while on the medication. The angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 44 publications
0
64
1
19
Order By: Relevance
“…The symptoms typically last for 24–72 hr, followed by spontaneous remission. The incidence of ACEi‐induced angioedema is relatively low (approximately 0.2–0.7%) with higher chance in older patients and in females as compared to males . Importantly, African Americans are four to five times more likely than Caucasians to experience angioedema.…”
Section: Drug Affecting Primarily the Vascular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms typically last for 24–72 hr, followed by spontaneous remission. The incidence of ACEi‐induced angioedema is relatively low (approximately 0.2–0.7%) with higher chance in older patients and in females as compared to males . Importantly, African Americans are four to five times more likely than Caucasians to experience angioedema.…”
Section: Drug Affecting Primarily the Vascular Systemmentioning
confidence: 99%
“…Common treatments for histamine‐mediated angioedema (such as antihistamines and glucocorticoids) are not effective in this setting. A risk of angioedema has been also described for angiotensin receptor blockers, but seems to be significantly lower (0.1%) with a low incidence of cross‐reactivity (<10%) . The mechanisms are thus much less clear.…”
Section: Drug Affecting Primarily the Vascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulating roles of SP in baroreflex have been well reviewed . Recent observations have shown that SP may play a major role in the secondary injury process following traumatic brain injury, particularly with respect to neuro‐inflammation, increased blood‐brain‐barrier permeability, and tissue edema due mainly to SP release‐mediated vasodilation and fluid extravasation into the tissues . This secondary pathophysiological process may subsequently change the blood pressure to noxious level.…”
Section: Introductionmentioning
confidence: 99%
“…AE manifestation in the upper airway region can be life-threatening due to its unpredictable clinical course. ACE is one of the main degradation enzymes of bradykinin – therefore, it is assumed that the iatrogenic inhibition of ACE leads to an increase in bradykinin levels [7]. Bradykinin in turn signals mainly via the constitutively expressed bradykinin receptor B 2 (B2R) and leads to vasodilatation and increases vascular permeability [8].…”
Section: Introductionmentioning
confidence: 99%